Α9‐ and α7‐containing receptors mediate the pro‐proliferative effects of nicotine in the A549 adenocarcinoma cell line. (8th September 2017) - Mucchietto, Vanessa; Fasoli, Francesca; Pucci, Susanna; Moretti, Milena; Benfante, Roberta; Maroli, Annalisa; Di Lascio, Simona; Bolchi, Cristiano; Pallavicini, Marco; Dowell, Cheryl; McIntosh, Michael; Clementi, Francesco; et al.
Abstract : Background and Purpose: Tobacco smoke contains many classes of carcinogens and although nicotine is unable to initiate tumourigenesis in humans and rodents, it promotes tumour growth and metastasis in lung tumours by acting on neuronal nicotinic ACh receptors (nAChRs). The aim of this study was to identify molecularly, biochemically and pharmacologically which nAChR subtypes are expressed and functionally activated by nicotine in lung cancer cell lines. Experimental Approach: We used A549 and H1975 adenocarcinoma cell lines derived from lung tumours to test the in vitro effects of nicotine, and nAChR subtype‐specific peptides and compounds. Key Results: The two adenocarcinoma cell lines express distinctive nAChR subtypes, and this affects their nicotine‐induced proliferation. In A549 cells, nAChRs containing the α7 or α9 subunits not only regulate nicotine‐induced cell proliferation but also the activation of the Akt and ERK pathways. Blocking these nAChRs by means of subtype‐specific peptides, or silencing their expression by means of subunit‐specific siRNAs, abolishes nicotine‐induced proliferation and signalling. Moreover, we found that the α7 antagonist MG624 also acts on α9–α10 nAChRs, blocks the effects of nicotine on A549 cells and has dose‐dependent cytotoxic activity. Conclusions and Implications: These results highlight the pathophysiological role of α7‐ and α9‐containing receptors in promoting non‐small cell lung carcinoma cell growth and intracellular signalling and provide a framework for the development of new drugs that specifically target the receptors expressed in lung tumours. Linked Articles: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc